EFEKTIVITAS DRAMA SEBAGAI METODE PENGAJARAN KEMAHIRAN BERBICARA BAHASA JEPANG PADA MAHASISWA - Mugiyanti, Mugiyanti; Karyati, Alo (Universitas Pakuan, 2024)
This research aims to find out the level of effectiveness and how students respond to the use of drama as a teaching method in the Kaiwa 1 course. Teaching Japanese speaking skills is aimed at improving speaking or communication skills, increasing proficiency in the use of vocabulary, deepening the application of grammar, and perfecting pronunciation., as well as practicing the ability to listen to what is heard from the person you are talking to. In this research, drama will be used as a teaching method for kaiwa. In drama, creativity is needed from both the teacher and students. Teachers must come up with ideas adapted to the conversation themes being studied in the Minna no Nihongo textbook. Apart from that, students also must be creative in developing conversation themes. The research method used in this research is a mixed method. The type of research is pure experimentation. The population and sample in this research were 25 first semester students of the Japanese literature study program, class 1A. The instruments in this research consisted of a pretest, treatment in the form of training and drama performances, posttest and questionnaires. Data collection was carried out by processing the results of the pretest and posttest, as well as distributing questionnaires in the form of questions to the students who the research samples were. The results of this research are expected to improve the ability to speak Japanese at elementary level students. Keywords: Drama; effectiveness; Japanese kaiwa; speaking ability